Differences in pre-planned agility and reactive agility performance in sport games - Jaromír Šimonek; Pavol Horička; Ján Hianik (Palacký University Olomouc, 2016)
Background: Authors in their contribution point to the differences in the methods of measurement of agility in the practice. Based on the experience of coaches as well as on their own experience have come to the conclusion that the Illinois Agility Test, which has long been used for the testing of agility in fact does not measure perception abilities and decision-making processes, since motor activity performed during the testing procedure represents a closed skill, where the only task of the tested person is to accelerate, decelerate and change the direction of running, while the task is known in advance. On the contrary, some authors recommend the testing of agility using apparatuses measuring selective reaction, such as Fitro Agility Check. Objective: The aim of the research was to find out differences in the performance of players from the point of view of sport specialization and also to assess the relationship between the performance of players in two agility tests (Illinois Agility Test, measuring the ability of simple reaction, acceleration, deceleration and changes of movement direction, as well as Fitro Agility Check, measuring the above mentioned processes plus the ones of perception and decision-making). Methods: The sample comprised basketball (G1), volleyball (G2) and soccer (G3) players (N = 55 boys, Mage = 15.78 years, age range = 14-17 years) from sport clubs in Slovakia. Illinois Agility Test (IAT) was used for testing acceleration and deceleration speed, simple reaction as well as changes of direction. Time of the trial was recorded by Microgate photocells. Fitro Agility Check (FAC) was used for the testing of reactive agility. Differences between independent groups were assessed using Kruskal-Wallis H test, or Mann-Whitney U test. Non-parametric Spearman correlation coefficient was used for detecting whether any correlation between the two variables exists (results in FAC vs IAT). Results: The greatest differences were found between the performances of players in IAT, on the contrary in the test FAC we found agreement in performances of players of different specializations. The value of statistical significance (p = .774) point to the non-existence of a relationship between the performance in IAT vs FAC and stress fundamental difference between both variables. Conclusions: This study provides evidence supporting the experience of coaches that when developing agility it is inevitable to transfer from performing exercises with the change of direction planned in advance realized in static conditions onto the practice of open skills, in which reaction to the changing conditions of the match is combined with anticipation of the resulting optimum solution of the given situation.